A CASE SERIES OF CAESAREAN MYOMECTOMY AT A TERTIARY CARE CENTRE IN KOLKATA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Caesarean myomectomy is still approached cautiously because of the perceived risk of haemorrhage and perioperative morbidity. With improved anaesthesia, uterotonics, surgical technique, and blood-product support, selected cases may be managed safely. This case series assessed outcomes of caesarean myomectomy at a tertiary care centre in Kolkata. Aim: To assess the operative risk and clinical benefits of caesarean myomectomy in selected pregnant women with uterine fibroids. Methods: This retrospective case series included 15 pregnant women with antenatally diagnosed fibroids who underwent myomectomy during caesarean section at Binayak Multispeciality Hospital, Kolkata, from March 2025 to March 2026. Records were reviewed for age, parity, gestational age, fibroid characteristics, blood loss, postoperative stay, transfusion, hysterectomy, and complications. Results: The mean maternal age was about 30 years, and the mean gestational age at delivery was 38 weeks. Fibroids measured 3–7 cm, with the largest measuring 6 × 7 cm. Most were anterior, while fundal and posterior fibroids were also seen. The average number removed was 2–3 per patient, and two women had more than eight myomas removed. Estimated blood loss was usually 600–800 mL, with one case reaching 1000 mL. No patient required blood transfusion, hysterectomy, or stepwise devascularisation. Operative time increased by nearly 20–30 minutes, but postoperative stay remained similar to routine caesarean delivery. Conclusion: Caesarean myomectomy appears feasible in selected patients when performed by experienced obstetricians with adequate surgical and blood-bank support.